Biology and the beast? The white man's quest for physical dominance in early twentieth-century America. Issue 4 (2nd October 2018) - Heffernan, Conor
ABSTRACT: Drawing on the relatively nascent world of animal history, the present article seeks to demonstrate how interactions between humans and nonhumans served to both reinforce and destabilise ideas of masculinity within American society. It does so through an examination of three unusual athletic case studies, spanning the period 1893 to 1926. Beginning with Eugen Sandow's infamous wrestling bout with Commodore the lion, the article goes on to explore the phenomenon of bear wrestling within the American circus before finally discussing John Bauman's 1923 and 1926 biological experiments pitting man against chimpanzee. Though these athletic contests were unconventional, even by the standards of the day, they served as arenas for predominately white men to display their masculinity. The article thus builds on previous gender and sporting histories, which have viewed physical activity as a means for men to establish their dominance over women and other men during this period. Expanding on this, the article demonstrates the role of nonhumans in this gender sculpting process in the hope of bringing animals even closer to the mainstream.